PATTERNS OF METHAMPHETAMINE USE AND ITS ASSOCIATIONS WITH PSYCHIATRIC SYMPTOMS IN PATIENTS UPON ADMISSION AT THE NATIONAL REHABILITATION CENTER LIDO BOGOR, INDONESIA - ROHMANIKA; AROZAL, WAWAIMULI; LOUISA, MELVA; GAYATRI, ANGGI; KEKALIH, ARIA; MARZUKI HY, JEFMAN EFENDI; LESTARI, ERNIAWATI; UTAMI, DIAH SETIA (International Journal of Applied Pharmaceutics, 2022)
Objective: Methamphetamine (MA) is a substance that is heavily abused worldwide. This present study aimed to investigate the association between the patterns of methamphetamine use and psychiatric symptoms in patients upon admission at The National Rehabilitation Center, Lido Bogor. Methods: This was a cross-sectional study of MA abusers during the period of January 2016–December 2018 at The National Rehabilitation Center, Lido, Bogor. This study was done by assessing medical records. The inclusion criteria were MA abusers at the age of 18 y and above. Assessment of psychiatric symptoms was evaluated using Addiction Severity Index (ASI). Microsoft Excel and SPSS version 22.0 were used to process the data. Results: The inclusion criteria were fulfilled by 1842 MA abusers. We found that 770 (41.8%) of MA abusers were assessed with psychiatric symptoms according to ASI. Depression was the most prevalent psychiatric symptom (31.9%), followed by anxiety (24.5%), and psychosis (8.9%). According to the results of multivariate analysis, the demographic profile and the mode of MA administration that are associated with the psychiatric symptoms were: female [odds ratio (OR): 1.95; 95% confidence interval (CI): 1.25–2.96, p<0.001], 5-year duration of use [OR 1.43; 95% CI: 1.43 (1.19–1.73), p<0.001], smoking as the route of administration [OR 1.3; 95% CI: 1.08–1.56, p<0.001, p = 0.006], and concomitant use with other narcotics [OR 1.76; 95% CI: 1.46–2.13, p<0.001]. Conclusion: Among MA abusers admitted to The National Rehabilitation Center, the main factors associated with psychiatric symptoms were: female, long duration of use, smoking as the route of administration, and concomitant use with other narcotics.